The The Overview of Knowledge Level of Seven Semester Students of Anesthesiology Nursing Study Program on Evidence Based Practice 2 Course At Harapan Bangsa University Purwokerto: English - Area Dhiatamaa, Sketsa; Sukmaningtyas, Wilis; Burhan, Asmat (Java Nursing Journal, 2023)
Background Evidence Based Practice (EBP) is scientific evidence with clinical expertise, pathophysiological knowledge, knowledge of psychosocial issues, and patient preference decision making. Based on data from WHO and the European Commission, health and social services must be supported by the best research evidence. Evidence Based Practice (EBP) plays an integral role in health care and has been recognized internationally as an ideal problem-solving approach. The ability of students to engage in understanding Evidence Based Practice is also still low, faculty in Iran who explain that knowledge of students involved regarding Evidence Based Practice is still low (47.1%). Meanwhile, undergraduate students' understanding of the main evidence-based practices in terms of assessment, discovery, and research applications is still low, namely (39%). Objective: To determine the level of knowledge of students of the Fellowship Study Program in the 7th semester of the applied undergraduate program regarding the Evidence Based Practice 2 course at Harapan Bangsa University. Methods: This study used a quantitative method with a cross sectional approach. The sample in this study used a non-probability sampling technique with a total sampling of 151 respondents. Results : The most dominant age of respondents with a good level of knowledge in the Evidence Based Practice 2 course in this study was 21-22 years old, with a percentage of 112 respondents (94.1%), gender with a good level of knowledge in the Evidence Based course The most dominant Practice 2 in this study was female, as many as 75 respondents with a percentage of (93.8%), the level of knowledge of respondents in the Evidence Based Practice 2 course in this study. The most dominant were respondents with a good level of knowledge, as many as 138 respondents with a percentage (91.4%).